2008
DOI: 10.1021/ic700911y
|View full text |Cite
|
Sign up to set email alerts
|

Ru Complexes That Can Catalytically Oxidize Water to Molecular Dioxygen

Abstract: The main objective of this review is to give a general overview of the structure, electrochemistry (when available), and catalytic performance of the Ru complexes, which are capable of oxidizing water to molecular dioxygen, and to highlight their more relevant features. The description of the Ru catalysts is mainly divided into complexes that contain a Ru-O-Ru bridging group and those that do not. Finally a few conclusions are drawn from the global description of all of the catalysts presented here, and some g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
106
1
3

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(113 citation statements)
references
References 76 publications
3
106
1
3
Order By: Relevance
“…Formation. Accumulated experimental and theoretical studies (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) on artificial photosynthesis systems have elucidated dual possible mechanisms of the water splitting reaction: (i) the radical coupling (RC) mechanism and (ii) the acid-base mechanism. Tanaka and coworkers have proposed the former mechanism for the water splitting reaction by their Ru-quinone complexes as illustrated in Fig.…”
Section: Possible Electronic and Spin States Of Mononuclear And Binucmentioning
confidence: 99%
See 2 more Smart Citations
“…Formation. Accumulated experimental and theoretical studies (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) on artificial photosynthesis systems have elucidated dual possible mechanisms of the water splitting reaction: (i) the radical coupling (RC) mechanism and (ii) the acid-base mechanism. Tanaka and coworkers have proposed the former mechanism for the water splitting reaction by their Ru-quinone complexes as illustrated in Fig.…”
Section: Possible Electronic and Spin States Of Mononuclear And Binucmentioning
confidence: 99%
“…In the past decades, a number of experimental and theoretical studies (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) have been performed to design artificial photosynthetic systems that mimic native PSII systems. Many binuclear transition-metal catalysts such as LðH 2 OÞM-O-MðOH 2 ÞL or LðH 2 OÞM-BL-MðOH 2 Þ (where L and BL are nonbridging and bridging organic ligands, respectively) were prepared and characterized for their catalytic properties toward water oxidation (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Complementing the work on Mn has been the earlier discovery that ruthenium-based catalysts, such as the "blue dimer," that can photooxidize water to dioxygen (Gersten et al 1982;Liu et al 2008;Romero et al 2008), and the recent spectacular work of Duan et al (2012), which has reported a rationally designed Rubased catalyst with an unprecedented turnover rate of 300 per sec, comparable to that of PSII. But perhaps the most practical catalysts for water splitting are based on Co, a relatively abundant element.…”
Section: Artificial Photosynthesismentioning
confidence: 99%
“…Among several metal cations, ruthenium ion is widely used in many applications including catalyst 1,2 , dyesensitized solar cell [3][4][5] , and in medicine as an anticancer agent [6][7][8] . However, extensive use of ruthenium ion could lead to accumulation of wastes harmful to the environment, as ruthenium ion exhibits various forms of toxicity 9 .…”
Section: Introductionmentioning
confidence: 99%